Mr Americana: reflections of American youth cultural identity through the Archie franchise from the 1940s to 1955 - Han, Gavin Burmeister Hann Deng (Nanyang Technological University, 2025)
This thesis explores the ways in which the Archie franchise reflected American youth culture during the 1940s and 1950s, a time marked by wartime anxieties and postwar consumerism. In 1946, MLJ Magazines decided to overhaul its brand image, renaming itself to Archie Comics Publications; shifting its focus from patriotic superheroes to the relatable experiences of Archie Andrews and his teenage friends in the fictional suburban town of Riverdale. By providing humour and escapism, the company grew and gave Archie his own franchise, signifying its status as a cultural icon that resonated with American adolescents.